Chest Trauma Score of Thoracic Trauma Patients in Dr. Mohammad Hoesin General Hospital Palembang January-June 2020 - Satria Marrantiza; Ahmat Umar; Bermansyah; Gama Satria; Aswin Nugraha (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2021)
Introduction: Thoracic trauma has mortality rates varying from 10% to 60%. Various scoring frameworks have been created for prognostic value in thoracic trauma patients, including the chest trauma score (CTS). This has not been studied in Indonesian patients. The authors decided to study the picture of CTS in thoracic trauma patients in the Indonesian subpopulation, especially in our hospital. Methods: This research is an analytical observational study at dr. Mohammad Hoesin (RSMH) Palembang in January-June 2020. Our research variables are age, lung contusions, number of rib fractures, bilateral rib fractures, and Chest Trauma Score (CTS). 37 cases could be analyzed with the length of stay, ICU care, mortality, and surgery option. Results: The most common thoracic trauma occurred at the age between less than 45 years, the highest degree of lung contusions was unilateral minor lung contusions. The most common rib fractures were <3 rib fractures. Chest Trauma Score in this study were less than 5. The CTS score had a significant relationship with length of stay and the need of ICU, but was not significantly associated with mortality and surgery option. Conclusion: Chest trauma score can be used to consider the length of treatment and priority needs of the ICU which will be prepared for the management of thoracic trauma patients, especially the young who are accompanied by lung contusions and rib fractures.